The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/8376979
|View full text |Cite
|
Sign up to set email alerts
|

Is GERD a Factor in Osteonecrosis of the Jaw? Evidence of Pathology Linked to G6PD Deficiency and Sulfomucins

Abstract: Osteonecrosis of the jaw (ONJ), a rare side effect of bisphosphonate therapy, is a debilitating disorder with a poorly understood etiology. FDA's Adverse Event Reporting System (FAERS) provides the opportunity to investigate this disease. Our goals were to analyze FAERS data to discover possible relationships between ONJ and specific conditions and drugs and then to consult the scientific literature to deduce biological explanations. Our methodology revealed a very strong association between gastroesophageal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…Risk factors for BRONJ include DM, cancer and the use of corticosteroids, immunosuppressants and radiotherapy. A significant association between ONJ and SS was observed in a recent study analysing the Food and Drug Administration (FDA’s) Adverse Event Reporting System 16. In this study, we further confirmed that patients with SS were susceptible to BRONJ after tooth extraction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Risk factors for BRONJ include DM, cancer and the use of corticosteroids, immunosuppressants and radiotherapy. A significant association between ONJ and SS was observed in a recent study analysing the Food and Drug Administration (FDA’s) Adverse Event Reporting System 16. In this study, we further confirmed that patients with SS were susceptible to BRONJ after tooth extraction.…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, there were no differences in tooth extraction between patients with and without SS. Low saliva flow combined with acid reflux could lead to a low pH in the oral cavity and overgrowth of acidophilic pathogens, which promote tooth decay and mucosal erosion 16. Even when patients with cancer were excluded, the use of BPs, suppuration and extractions remained associated with ONJ 19.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that patients with SS were more susceptible to bisphosphonate-related osteonecrosis of the jaw, which might be due to the shared risk factors and molecular pathways ( 25 , 27 ). Low salivary flow in combination with acid reflux might result in an oral environment of low pH, which promotes the growth of acidophilic bacteria, in turn, leading to tooth destruction and mucosal degradation ( 40 ). Even in low dosages, these drugs can exert a considerable influence on the expression of genes that play a role in the differentiation and growth of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…4 A). During bone resorption, the proton pump in the OC trap produces an acidic environment, which significantly increases the association of BPs with HA crystal [ 46 ]. OCs take up the released BPs via liquid phase endocytosis [ 47 ].…”
Section: Mechanism Of Bps In Regulating Bone Homeostasismentioning
confidence: 99%